2021
DOI: 10.1039/d0cc08144b
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitive pressure-dependence of the conversion temperature of hysteretic valence tautomeric manganese–nitronyl nitroxide radical 2D-frameworks

Abstract: Under a mild external pressure of 0.1 GPa valence tautomeric compounds {[Mn2(NITIm)3]X}n with nitronyl nitroxide radical NITIm and X = ClO4− or BF4− have their conversion shifted upwards by almost 40 K with respect to room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…[69] more than 40 years ago. Later, others groups [26,63,[70][71][72] reported this anomalous (non-conventional) behavior and another variety of behaviors, such as an hysteresis under pressure which shifts at constant width to higher temperatures [71,73], or vanishing small hysteresis which reappears at higher pressure [71,74], which could be described as a reentrant phenomenon. Others spin transition behaviors with applied pressure can be found in the literature such as pressure-induced two-step transition [22,[75][76][77] but also the pressure can induce possible crystallographic transitions which then alters the intermolecular packing, or which even lead to symmetry breaking [76,[78][79][80], although most of the induced transformations are isostructural.…”
Section: Introductionmentioning
confidence: 96%
“…[69] more than 40 years ago. Later, others groups [26,63,[70][71][72] reported this anomalous (non-conventional) behavior and another variety of behaviors, such as an hysteresis under pressure which shifts at constant width to higher temperatures [71,73], or vanishing small hysteresis which reappears at higher pressure [71,74], which could be described as a reentrant phenomenon. Others spin transition behaviors with applied pressure can be found in the literature such as pressure-induced two-step transition [22,[75][76][77] but also the pressure can induce possible crystallographic transitions which then alters the intermolecular packing, or which even lead to symmetry breaking [76,[78][79][80], although most of the induced transformations are isostructural.…”
Section: Introductionmentioning
confidence: 96%
“…Although the NO group is a weak Lewis base, coordination is effective by using electron-withdrawing ancillary ligands on the metal center, such as hexafluoroacetylacetone, or by incorporating the NO group into a chelate so that such extra ligand can be removed from the coordination sphere [ 11 ]. The nitronyl nitroxide stability in coordination compounds could be tempered after the discovery of valence tautomerism in some 2D coordination polymers with manganese(II), where nitronyl nitroxide radical is reduced on cooling [ 24 , 25 , 26 ]. However, the process reverses on reheating.…”
Section: Introductionmentioning
confidence: 99%
“…Research on metal-nitronyl nitroxide systems has led to the discovery of two other phenomena out of the classical magnetism relying on the interplay of magnetic interaction. These are molecular-spin transitions in some copper(II) complexes [ 42 , 43 , 44 ] and valence tautomerism in some manganese(II) coordination polymers [ 24 , 25 , 26 ]. Metal-nitronyl nitroxide coordination chemistry is, therefore, a versatile tool for different types of bistable systems [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…41,42 In addition, the single-chain magnet behavior in VT iron-tetraoxolene complexes 43,44 and the pressure-dependent electron transfer in manganesenitronyl nitroxide derivatives were characterized in the solidstate form. 45,46 These emerging studies stimulate the further explorations of VT complexes. Magnetic analyses revealed that compound 1 exhibits onestep VT behavior (Figure 1).…”
mentioning
confidence: 98%
“…For example, Li et al constructed a novel radical-rich cobalt VT triangle, and further integrated VT behavior into a metal–organic framework . Sato et al demonstrated a macroscopic polarization change in a mononuclear VT complex and a peculiar pyroelectric behavior in a polar [FeCo] complex. , In addition, the single-chain magnet behavior in VT iron-tetraoxolene complexes , and the pressure-dependent electron transfer in manganese-nitronyl nitroxide derivatives were characterized in the solid-state form. , These emerging studies stimulate the further explorations of VT complexes.…”
mentioning
confidence: 99%